Brave (Parrogon Books Ltd, 2014)
Merida is a free-spirited princess in search of adventure. When her mother wants her to marry, this rebellious redhead sets out to change her mind with a surprising result! Can the bond between mother and daughter be mended in time?
Keywords: Juvenile Fiction / Adventure